Spring phytoplankton and periphyton composition: case study from a thermally abnormal lakes in Western Poland - Burchardt, Lubomira; Hindák, František; Komárek, Jiří; Lange-Bertalot, Horst; Messyasz, Beata; Pikosz, Marta; Wejnerowski, Łukasz; Jakubas, Emilia; Rybak, Andrzej; Gąbka, Maciej (Biodiversity: Research and Conservation, 2015)
Getting to know the response of different groups of aquatic organisms tested in altered thermal environments to environmental conditions makes it possible to understand processes of adaptation and limitation factors such as temperature and light. Field sites were located in three thermally abnormal lakes (cooling system of power plants), in eastern part of Wielkopolska region (western Poland): Pątnowskie, Wąsosko-Mikorzyńskie and Licheńskie. Water temperatures of these lakes do not fall below 10°C throughout the year, and the surface water temperature in spring is about 20˚C. In this study, we investigated the species structure of the spring phytoplankton community in a temperature gradient and analyzed diversity of periphyton collected from alien species (Vallisneria spiralis) and stones. 94 taxa belonging to 56 genera of algae (including phytoplankton and periphyton) were determined. The highest number of algae species were observed among Chlorophyta (49), Bacillariophyceae (34) and Cyanobacteria (6). In spite of important differences in temperature in the investigated lakes, taxonomic composition of phytoplankton was comparable. Thermophilic species: Glochidinium penardiforme and Cylindrospermopsis raciborskii were found in the species structure (blooms were not observed). The obtained data also showed that the biotic surface of Vallisneria spiralis was a better substrate for Bacillariophyceae colonization than stones. The examination in the spring season of these thermally altered lakes, indicated the taxonomic composition of phytoplankton typical for eutrophic reservoirs (not heated). There was no replacement of any phytoplankton groups which are characteristic for spring conditions, even if there were changes in the competition dynamics.